Rancang Bangun Penyeimbang Arus Beban pada Sistem 3 Fasa Menggunakan Mikrokontroler Atmega 2560 - putra, agus mardiana; partha, gede indra; budiastra, i nyoman (Majalah Ilmiah Teknologi Elektro, 2016)
Abstract --The design of balancing the load current on three-phase systems using a microcontroller ATMega 2560 is a tool that serves to reduce the power loss due to the load current unbalance the current flows in the neutral phase on three-phase systems. The methods in making this tool is divided into two parts: first, the design of hardware consist of designing electronic components which are used by the current sensor circuits, relay, LCD (Liquid Crystal Display) etc. Second, the design of software is a tool listing program procedure including the monitoring program displays the current of each phase on LCD using the Arduino IDE. SCT013-030 current sensor used, the output of the current sensor is connected to the pin ADC (Analog to Digital Converter) microcontroller ATMega 2560. The result of the test design of balancing load current on three-phase system using a microcontroller ATMega 2560 which is balancing the load current by moving the channel load of sequence number load the smallest connected to the phase with the current biggest load toward a phase that has a load current smallest when neutral current exceeds the limit is permitted.
Keywords: Distance Learning; Balancing load current; monitoring system; SCT013-030; microcontroller ATMega 2560; channel load; neutral phase current.